Effect of Salt Applications on Plant Growth in Some Pole and Dwarf Bean Genotypes - Enes Fidan; Aytekin Ekincialp (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the responses of 20 different bean genotypes (13 pole and 7 dwarf) to salt (NaCl) stress at 0 mM, 25 mM and 50 mM were investigated. Salt application was performed together with irrigation water in the same time every day during 4 days. In the study, which was prepared according to randomized plot design with 3 replications, the plants were grown in the pots containing peat-perlite in a ratio of 2:1 under climatic conditions of 23±2°C. Root dry matter, root fresh and dry weight and some nutrient contents (Phosphorus-P, Copper-Cu, Zinc-Zn, Manganese-Mn, Iron-Fe and Magnesium-Mg) were investigated in order to determine salinity tolerance in bean genotypes. The data obtained from the study revealed that salt stress responds differently in both genotypes and applications. When the average of applications of 25 mM and 50 mM salt stress was examined, it was found that while root fresh and dry weight, root dry matter (%) and Fe content increased compared to control group, Mn and P content decreased. Among the genotypes exposed to salt stress, while four genotypes [two pole (numbered as 13 and 19) and two dwarf (numbered as 8 and 11)] were determined to be tolerant to salt, 3 genotypes [one pole (numbered as 14) and two dwarf (numbered as 18 and 20)] were evaluated as sensitive.